The social theater as an inclusive educational-educational device: Theoretical and practical analysis of social theater for the development of the intellectual welfare of communities - Mulè, Paolina (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this short essay the A. intends to analyze the scientific coordinates of social theater as a pedagogical-didactic device in an inclusive perspective for the development of the intellectual welfare of communities in the 21st century. The reference model is that of Inclusive Education, which represents, as Unesco has specified several times, a true guideline in the field of education, education and training; it develops through the guiding principles of equality, social justice, freedom, the right to citizenship, the right to education and social equity, without any discrimination based on race, gender, language, or different cultures. This is possible through inclusive theater workshops at school.